Persepektif Masyarakat Terhadap Peran Bela Negara Dalam Menjaga Kedaulatan Indonesia di Laut Natuna Utara - Dania Agustini; Dewi Ari Astuti; Irma Suryani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The North Natuna Sea is a strategic area that has significant economic and geopolitical value for Indonesia. The area is often at the centre of attention due to the various security challenges it faces, including threats from illegal activities such as fishing by foreign vessels. The purpose of this study is to examine the community's perspective on the role of state defence in maintaining Indonesia's sovereignty in the North Natuna Sea. Due to its exploratory nature, this study was conducted using a qualitative method by collecting descriptive data. Data was collected through randomly distributed questionnaires from various layers of Indonesian society, including students, security forces, community leaders, and local residents. Data was analysed using inferential and descriptive statistical techniques to identify people's perceptions, attitudes and awareness levels regarding the importance of the role of state defence. The study found that most respondents had a positive view of the role of state defence and realised its importance in maintaining the sovereignty of Indonesia's territorial waters. The findings provide important implications for policy makers in formulating strategies and educational programmes to increase public participation in state defence.